Pendekatan Blended Learning Sebagai Strategi Pembelajaran Masa Depan - Riski Andrianingsih Mangidi (Prodi PGSD Unsultra, 2024)
Blended Learning (BL) is a learning approach that combines face-to-face learning with online learning. This approach has become a major concern in the development of 21st century education, especially after the rapid development of information and communication technology. This literature study aims to examine the application of Blended Learning in the context of education, identify its benefits, challenges faced, and recommendations for more optimal implementation. Based on the results of a study of various sources, it was found that Blended Learning can increase the effectiveness of learning, provide flexibility of time and place, and provide opportunities for a more personalized learning experience. However, its implementation requires teacher readiness, adequate technological infrastructure, and appropriate curriculum design.